CARDIAC FREQUENCY BEHAVIOUR OF STUDENTS IN THE 1000 METRE REDUCED SPACE TEST (Fiep Bulletin - online, 2015)
The objective of this study was to investigate the cardiac frequency behavior of male and female gender students when submitted to the 1000 meter reduced space sprint test (oval configuration), standardized by KRUG & NUNES (1994). The sample was randomly put together by 240 students of both genders, 120 students by gender and 30 students in each age group and gender, enrolled in public network schools in the city of Pelotas, RS.  The 1000 meter reduced space sprint test was used (oval configuration, limited to the rectangle of 14, 50 m X 10 m), with the objective of measuring aerobic power. Body Weight (BW) data was collected as well as Stature (STR), Body Fat (F %), Fat (FBM) and thin (TBM) body mass, Cardiac Frequency at Rest (CFR), Maximum Cardiac Frequency (MCF), Reserve Cardiac Frequency (RCF), Maximum Cardiac Frequency Percentage (MCF %) and Cardiac Frequency Exertion after 30 seconds of sprinting (CFE % -30).  Faced with the collected results, it is understood that in the RCF, MCFE % -30 and MCFP % variables, the students of both genders from this study were maintained inside the physiological studies during the 1000 meter sprint, in no way compromising the cardio respiratory system.
Keywords: Maximum oxygen consumption; Cardiac frequency and Students.